DEVELOPMENT OF CONTEXTUAL LEARNING TOOL THEME OF VARIOUS WORKS TO TRAIN CREATIVE THINKING SKILLS AND STUDENT OUTCOMES GRADE IV PRIMARY SCHOOL - Pradana, Indra (STIT Al - Ibrohimy Bangkalan, 2019)
The purpose of this study is to describe the development of contextual learning tools of various occupations to train the ability of creative thinking and learning outcomes of fourth graders in SDN Kraton 2 Bangkalan. Validated learning tools were implemented to 30 students with one group pre-test-post test design. Instruments used in this study include: 1) the learning device validation sheet; 2) student activity observation sheets; 3) questionnaire of student response; 4) instrument of creative thinking ability test; 5) test result learning instruments. Creative thinking skills produce a narrative. While the technique of data analysis using inferential analysis to know the difference of test result of creative thinking skill and learning result between control group and experiment group using t-test analysis. The quality of the developed device is evident from the assessment of expert validators who get good results for use. While the practicality of the device is evident from the observation of student activity during the learning process that gets a percentage of 83% of students who are active in learning. The effectiveness of instructional tools obtained from the test results of students who get a significance value of 0,000 <0.05 for creative thinking skills, while for learning results obtained a significance value of 0.020 <0.05.